Effect of inlet air temperature on SI engine fueled with diethyl ether-gasoline blends - S. Srihari; D. Sanjay Kumar; Thirumalini S (Journal of Mechanical Engineering and Sciences, 2018)
In this study the performance and emission characteristics of spark ignition genset engine fueled with gasoline and diethyl ether (DEE) blends are carried out. The DEE blends are varied from 3%, 6% and 9% by volume in gasoline. A four-stroke single cylinder constant speed spark ignition engine is used for the experiments. The variation in fuel consumption and exhaust emission with respect to two different inlet air temperatures are studied. The concentration of exhaust emissions such as HC, CO, NOx is observed. The parameters such as inlet air temperature, brake specific fuel consumption, relative air to fuel ratio are also measured. It is noticed that 6% DEE blend in gasoline reduced almost reduced HC emission about 57% and also considerable reduction in CO emission at lower air intake temperature. The addition of diethyl ether has an improvement in performance and significant reduction in HC, CO and NOx emissions.